The theory of justice in the history of political thought as the main argument for the destruction of corruption and public discontent (Part first) - Zhansugurova, Zh.; Montaner, Ramos (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2019)
The category of justice is more than a political concept. Based on an analysis of political thought from various historical eras and using complex historical and naturalistic approaches, the authors conclude that this category has a deeply natural meaning and has the right to be law for society, for its institutions and citizens. They should be permeated with the whole of nature and the essence of the political system and personality as parts of a whole. “The laws of nature existed before the laws of men – they are only constant.. social laws can only be called fair, when they are agreed with them” (Footnote in the text, author’s note). The initial understanding of the importance of the principles of the theory of justice that has taken shape over the centuries, and its impact on the eradication of corruption, and thus the weakening of public discontent, is, in the opinion of the authors, the main task of this study. This article is the first theoretical part of a political science study, introducing an experimental part, which will be devoted to the perception of the phenomenon of “corruption” by respondents from Kazakhstan and Spain and a comparative country assessment of the impact of corruption risks on society and government in these countries. Key words: theory of justice, corruption, political thought, history, power, citizen, society, truth, values.